1997
DOI: 10.1093/oxfordjournals.aje.a009225
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Cognitive Lifetime Drinking History

Abstract: A new measure of lifetime alcohol consumption, the Cognitive Lifetime Drinking History (CLDH) uses beverage-specific questions on drink sizes and assesses drinking patterns to enhance recall. Two methods of establishing drinking intervals were examined: 1) floating--the respondent's report of when drinking changed, and 2) fixed--defined in terms of decades. Test-retest reliability for lifetime ounces of alcohol consumed and times intoxicated in lifetime estimated at visits 1 week or more apart was assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 13 publications
2
72
0
Order By: Relevance
“…The recent fi nding-that including diet measures in models of diabetes risk biased results toward a smaller protective effect (Imamura et al, 2009)-suggests that including dietary measures would not have eliminated our fi ndings regarding diabetes. Although alcohol-consumption patterns are assessed through multiple and detailed questions in the 2005 National Alcohol Survey, the lifetime measures used in the analyses are retrospective and may, therefore, be subject to recall bias downward (Caldwell et al, 2006;Lemmens et al, 1997;Rehm et al, 2008;Russell et al, 1997), leading to some degree of misclassifi cation. Because of sample-size limitations, we are not able to estimate separate models by gender or race/ethnicity group.…”
Section: Discussionmentioning
confidence: 99%
“…The recent fi nding-that including diet measures in models of diabetes risk biased results toward a smaller protective effect (Imamura et al, 2009)-suggests that including dietary measures would not have eliminated our fi ndings regarding diabetes. Although alcohol-consumption patterns are assessed through multiple and detailed questions in the 2005 National Alcohol Survey, the lifetime measures used in the analyses are retrospective and may, therefore, be subject to recall bias downward (Caldwell et al, 2006;Lemmens et al, 1997;Rehm et al, 2008;Russell et al, 1997), leading to some degree of misclassifi cation. Because of sample-size limitations, we are not able to estimate separate models by gender or race/ethnicity group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cumulative life-time consumption based on a more elaborate, time-consuming 'floating' format involving potential changes in drinking associated with important life events, specifically recalled, correlated in the 0.80s or high 0.70s with equivalent measures derived from a simpler 'fixed' version asking about decades of life [134]. Thus, survey applications of the simpler, fixed period-based variety are feasible [3,135].…”
Section: Life-time Measures Of Alcohol Consumptionmentioning
confidence: 99%
“…Adjusted volumes based on container size and pour level were estimated with a photographic method adapted from Russell et al (1997). Although pouring methods (e.g., Kerr et al, 2009) have been shown to be most accurate, photographic methods are a suffi cient alternative when time or resource constraints preclude more involved approaches (see Kaskutas and Kerr, 2008, for a validation study).…”
Section: Unadjusted Alcohol Consumption Variablesmentioning
confidence: 99%